Network+ study guide & practice exams exam N10-003 - Shimonski, Robert; Cross, Michael, 1965-; Hunter, Laura E. (Rockland, MA : Syngress ; [Sebastopol, CA] : Distributed by O'Reilly Media, 2005)
The Network+ Study Guide covers all the objectives on the CompTIA exam, including the features and functions of networking components, and ensuring that readers have the knowledge and skills needed to install, configure and troubleshoot basic networking hardware, protocols and services. It covers exam topics such as media and topologies, protocols and standards, network implementation, and network support, as well as new exam topics on technologies such as wireless networking and Ethernet. * Complete coverage of the new 2005 exam, written from the ground up * Competitively priced with additional interactive exams online * Popular exam being revised for first time since 2001.
Introduction ; Domain I Media and Topologies ; Network Fundamentals ; Network Media ; Network Devices ; Wireless Technologies ; Domain II Protocols and Standards ; OSI Model ; Network Protocols ; WAN and Security Standards and Services ; Network Operating Systems ; Domain III Network Implementation ; Network Infrastructure and Security ; Fault Management and Disaster Recovery ; Domain IV Network Support ; Network Troubleshooting Tools ; Network Troubleshooting Methodology ; Self Test Appendix ; Index.
Includes index.
Keywords: Electronic data processing personnel -- Certification; Telecommunications engineers -- Examinations -- Study guides; Computer networks -- Examinations -- Study guides; Electronic books